Human Healthcare and Its Pharmacy Component from a Safety Point of View - Tkachenko, N. O.; Pankevych, O.; Mahamova, T. V.; Hromovyk, B.; Lesyk, R.; Lesyk, L.; Ткаченко, Наталя Олександрівна; Маганова, Тамара Валеріївна (My University, 2024)
Healthcare plays a crucial role in public and national safety as a significant part of state activity and a component of national safety, whose mission is to organize and ensure affordable medical care for the population. The four stages of the genesis of healthcare safety development with the corresponding safety models of formation were defined: technical, human factor or security management, systemic security management, and cognitive complexity. It was established that at all stages, little attention is paid to the issues of the formation of the pharmaceutical sector’s safety. Taking into account the development of safety models that arise during the four stages of the genesis of safety science, we have proposed a model of the evolution of pharmaceutical safety formation. At the same time, future research is proposed to focus on new holistic concepts of safety, such as “Safety II”, evaluation and validation methods, especially in the pharmaceutical sector, where the development of this topic remained in the second stage of the evolution of science, the search for pharmaceutical errors related to drugs.
Keywords: safety; public health; security; healthcare; pharmaceutical